2004
DOI: 10.1111/j.1527-3466.2004.tb00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Protective Effects of Resveratrol

Abstract: Resveratrol (3,4¢,5-trihydroxy-trans-stilbene), a phytoalexin found in grape skins, peanuts, and red wine, has been reported to have a wide range of biological and pharmacological properties. It has been speculated that at low doses (such as consumed in the common diet) resveratrol may have cardioprotective activity. In this article we describe recent in vitro and in vivo studies in animal models. The results of these studies suggest that resveratrol modulates vascular cell function, inhibits LDL oxidation, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
301
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(311 citation statements)
references
References 101 publications
(107 reference statements)
5
301
0
5
Order By: Relevance
“…Beneficial cardiovascular properties of this polyphenol have been described previously [15,19,20]. Furthermore, the chronic administration of resveratrol enhances aortic eNOS expression in obese Zucker rats.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Beneficial cardiovascular properties of this polyphenol have been described previously [15,19,20]. Furthermore, the chronic administration of resveratrol enhances aortic eNOS expression in obese Zucker rats.…”
Section: Discussionmentioning
confidence: 62%
“…It acts as a cancer chemoprevention agent [16], a powerful anti-inflammatory factor and an antioxidant agent [17,18]. Its cardiovascular properties, including inhibition of platelet aggregation and promotion of vasodilation by enhancing the production of NO [19] have also been described [15,20] and recent studies have reported its beneficial effects against ageing and metabolic diseases [21][22][23][24]. Resveratrol has been described as a potent activator of AMPK in several tissues and cell lines, i.e, HepG2 [24], C2C12 myotubes [25] neuronal cell lines and neurons [26].…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol (3,5,4'-trihydroxystilbene) is a polyphenol predominately found in red wine and grapes that has attracted much interest due to its cardioprotective potential shown in vivo (14)(15)(16). Resveratrol exists in cis-and trans-isomeric forms, but only trans-isomer is mainly present in wine (17), which can be found at highest concentration in grape skin in ranges between 50 and 400µg/g of fresh weight (18). Hence, trans-resveratrol is often used in clinical trials due to its stability in absence of ultra-violet light (17).…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol exists in cis-and trans-isomeric forms, but only trans-isomer is mainly present in wine (17), which can be found at highest concentration in grape skin in ranges between 50 and 400µg/g of fresh weight (18). Hence, trans-resveratrol is often used in clinical trials due to its stability in absence of ultra-violet light (17). Depending on the variety of grape used in wine making, the concentration of trans-resveratrol in red wine is between 0.1 and 14.0mg/L (19).…”
Section: Introductionmentioning
confidence: 99%
“…Biological benefits of resveratrol against cancer, cardiovascular disease, inflammation and ischaemic injuries, as well as enhancement of stress resistance and life span extension of various organisms from yeast to vertebrates has been reviewed (Baur and Sinclair 2006). It has been found that resveratrol modulates vascular cell function, inhibits LDL oxidation, suppresses platelet aggregation and reduces myocardial damage during ischemiareperfusion (Bradamante et al 2004). Physiological activity of cis-resveratrol was shown to inhibit kinase activity, a factor related to cancer (Jayatilake et al 1993).…”
Section: Introductionmentioning
confidence: 99%